Nordic diet and its benefits in neurological function: a systematic review of observational and intervention studies - Jafari, Reyhaneh Sadat; Behrouz, Vahideh (Frontiers in Nutrition, 2023)
Neurological disorders have been considered the major contributors to global long-term disability and lower quality of life. Lifestyle factors, such as dietary patterns, are increasingly recognized as important determinants of neurological function. Some dietary behaviors, such as Nordic diet (ND) were likely to have protective effects on brain function. The ND pattern is characterized by high intakes of different healthy food items including vegetables, fruits, whole-grain cereals, legumes, rapeseed oil, fish, and seafood. However, an understanding of the effectiveness of the ND pattern to improve neurological function and brain health is not fully understood. We review the current evidence that supports the ND pattern in various aspects of neurological function and addresses both proven and less established mechanisms of action based on its food ingredients and biochemical compounds.